Device and method for testing duration time and condensation strength of black ice on phase-change asphalt pavement

By designing a test device for phase-change asphalt pavement, using conductivity meter and pressure gauge, the problem of measuring the condensed time and intensity of black ice in the existing technology is solved, the precise test and intensity evaluation of black ice is achieved, and the low temperature is promoted Selection of suitable types and dosages of phase change materials.

CN119322086AActive Publication Date: 2025-01-17HOHAI UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411675755.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-17
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The prior art lacks devices and methods for quantitatively testing the condensed time, melting time and condensed strength of black ice, which makes it difficult to determine the types and dosages of low-temperature phase change materials, and the application of different climate regions is limited.

Method used

A test device including a head unit, a water tank unit and a collection unit is designed. The time when water freezes and ice melts is accurately measured using a conductivity meter, and the condensation strength of black ice is measured by a pressure gauge.

Benefits of technology

Accurate testing of the duration and condensation strength of black ice on phase-change asphalt pavement is achieved, and new mechanical indicators are provided to effectively characterize the condensation strength of black ice.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119322086A_ABST
    Figure CN119322086A_ABST
Patent Text Reader

Abstract

The invention provides a device and a method for testing black ice duration and coagulation strength on a phase-change asphalt pavement, and belongs to the technical field of pavement surface anti-freezing performance testing. The device comprises a pressure head unit, a water tank unit and a collection unit, wherein the pressure head unit comprises a hollow round pipe, a concentric variable-diameter special-shaped pipe, a round sheet, a steel ball, a round rod, a round barrel and a spring; the water tank unit comprises a fan-shaped water tank, a plastic film, a screw, a horizontal ruler and a horizontal adjusting foot with a screw rod; and the acquisition unit comprises a conductivity meter and a pressure meter. The test method comprises the following steps: carrying out a freeze-thaw test on the phase change asphalt mixture of which the bottom surface is coated with water films with different thicknesses, and testing the coagulation time, the thawing time and the duration time of black ice with different thicknesses according to a conductivity-time curve; pressing the black ice with different thicknesses until the black ice is broken, and testing the condensation strength of the black ice with different thicknesses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road surface anti-icing performance testing, and in particular relates to a detection device for determining the condensation state of black ice on a phase-change asphalt road surface. Background Art

[0002] In autumn and winter, black ice is very likely to appear on mountain roads, roads in humid areas, bridge pavement sections, shady sides and low-lying sections. On the one hand, black ice on the road surface greatly reduces the friction coefficient between vehicle tires and the road surface, causing the car to slip easily and difficult to control, significantly increasing the danger of driving the vehicle; on the other hand, black ice is very thin, and the black color of the road surface asphalt can be seen through it, resulting in low visibility of the ice surface, making it difficult to be discovered and effectively warned. Therefore, delaying the appearance of black ice on the road surface and accelerating the melting of black ice are difficult problems that road workers continue to pay attention to.

[0003] In order to achieve the slow setting and accelerated melting of the road surface, researchers have developed a low freezing point technology represented by salt-storage asphalt pavement. This technology is to add chloride-containing admixtures to the surface of the road surface. Its typical products include imported MFL and domestic LX. Through the continuous release of chloride salts in rainy and snowy weather, the freezing point of the road surface is lowered and the freezing of the road surface is delayed. At present, the production of salt-storage admixtures, the composition design of salt-storage asphalt concrete, and the construction technology of salt-storage asphalt pavement have matured. A certain number of salt-storage asphalt pavement test sections have been paved both at home and abroad, showing good slow setting performance in ice and snow weather. However, engineering practice has found that the slow setting function of salt-storage asphalt pavement can only last for 2 to 4 years. The main reason is that in spring and summer, chloride salts on the road surface are still precipitated and released, resulting in the chloride salt content in the road surface continuously decreasing over time.

[0004] In response to the problem of short duration of the slow setting function of salt storage pavement technology, technologies represented by phase change pavement have begun to appear in recent years. This technology is to add low-temperature phase change materials (phase change temperature between 0℃ and 5℃) to the pavement, and reduce the rate of temperature drop of the pavement when the temperature drops by storing heat during phase transition, so as to achieve the purpose of slow setting of the road surface. At present, this technology has achieved a series of results in the screening of low-temperature phase change materials, the evaluation of mechanical properties and road performance of phase change asphalt concrete, etc. However, the influence of the type and dosage of phase change materials on the setting time, melting time and setting strength of thin ice in low-temperature phase change asphalt concrete is still unclear, which makes it difficult to determine the appropriate type and dosage of low-temperature phase change materials for different climate regions, which largely hinders the application of low-temperature phase change asphalt concrete in sections prone to black ice.

[0005] The fundamental reason for the unclear influence of the type and dosage of phase change materials on the setting time, melting time and setting strength of black ice is that there is currently a lack of devices and methods for quantitatively testing the setting time, melting time and setting strength of black ice. The main manifestations are: (1) When the thickness of black ice is within 1 to 4 mm, it is difficult to determine the setting and melting by testing the temperature with a thermometer; the method of adding "ice crystal catalyst" and judging the setting time by observing the color change manually is also very subjective, and a high-precision method needs to be adopted to determine the time when water freezes and ice melts. (2) The small thickness of black ice makes it difficult to test the strength of black ice or the bonding strength between black ice and asphalt concrete by conventional test methods such as compression and pulling. New methods need to be invented to comprehensively evaluate the setting strength of black ice. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a testing device and method for the duration and condensation strength of black ice on a phase change asphalt pavement. By utilizing the property that the electrical conductivity of solid ice is much smaller than that of liquid water, a conductivity meter is used to accurately measure the moment when water freezes and ice melts. At the same time, a new testing method for the condensation strength of black ice is proposed.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0008] A testing device for the duration and condensation strength of black ice on a phase-change asphalt pavement includes: a pressure head unit, a water tank unit and a collection unit. The pressure head unit includes a hollow round tube, a concentric variable diameter special-shaped tube, a disc, a steel ball, a round rod, a cylinder, and a spring; the water tank unit includes a fan-shaped water tank, a plastic film, a screw, a level ruler, and a screw-type level adjustment foot; the collection unit includes a conductivity meter and a pressure gauge.

[0009] Furthermore, the pressure head unit is a hollow circular tube with a length of 6 cm and an outer diameter of 1.95 cm at the upper part, a through hole with a diameter of 5 mm is opened on the side 1 cm away from the top, and a thread is arranged on the inner wall of the circular tube within a range of 1 cm from the bottom; the lower part of the pressure head is a concentric variable diameter special-shaped tube, the outer side surface of the small-diameter circular tube is provided with a thread, which extends into the interior of the hollow circular tube and is screwed with the thread on the inner wall of the hollow circular tube, the outer diameter of the large-diameter circular tube is the same as the outer diameter of the hollow circular tube, and the side surface is opened along the height direction There are 8 incisions of equal depth. The inner wall of the large-aperture circular tube is provided with a thread within 1 cm from the upper edge of the incision, and is equipped with a disc that can be screwed thereon. The side and bottom surfaces of the disc are respectively engraved with threads and "cross"-shaped grooves, and after tightening, the bottom surface of the disc is flush with the upper edge of the incision; a conductivity probe is installed inside the pressure head, and the probe enters the pressure head from the through hole on the hollow circular tube, and is fixed on the inner wall of the hollow circular tube and the inner wall of the concentric reducer from top to bottom, and the bottom end of the probe is flush with the lower edge of the incision.

[0010] Furthermore, the steel ball has a through hole through the center of the ball, and is mounted on a round rod, and both ends of the round rod are fixed on the inner wall of the cylinder. The two cylinders form a group and are connected by a spring. Both ends of the spring are fixed on the bottom surfaces of the two cylinders, and after being fixed, the two round rods in the two cylinders are parallel to each other.

[0011] Furthermore, the pressure head unit consists of 4 groups, each group has 2 pressure heads, and the depth of the side cutout of the large-diameter circular tube in each group of pressure heads is 1 mm, 2 mm, 3 mm, and 4 mm, respectively.

[0012] Furthermore, the water tank unit is composed of 4 open fan-shaped water tanks with equal horizontal areas. The depths of the fan-shaped water tanks are 1mm, 2mm, 3mm, and 4mm respectively. The bottom plate thickness of each fan-shaped water tank is 2cm. There are two through holes with a hole diameter of 2cm. The inner wall of the hole is threaded. Each hole is equipped with a screw that can be screwed thereto, and after tightening, the top surface of the screw is flush with the bottom surface of the water tank.

[0013] Furthermore, the water tank is made of stainless steel, and glass wool with low thermal conductivity is pasted on the outer side.

[0014] Furthermore, the distances between the centers of the two through holes on the bottom plate of the fan-shaped water tank and the vertex of the fan are both 4.36 cm, and the vertical distances to the nearest radius of the fan are both 1.67 cm.

[0015] Furthermore, the number of installed level rulers is 2, and whether the level is in two vertical directions is detected at the same time.

[0016] Furthermore, the screw-type horizontal adjustment foot provides an integrated screw and ball head, the screw can adjust the overall length of the adjustment foot, and the ball head can adjust the angle of the screw.

[0017] Furthermore, the acquisition unit is composed of a pressure gauge and a conductivity meter. The pressure gauge must have a range greater than 2MPa and an accuracy higher than 0.1MPa. The conductivity meter must have more than 8 channels, a range greater than 200μS / cm, an accuracy higher than 1μS / cm, and an applicable temperature range of -10°C to 60°C.

[0018] Furthermore, the test method of the present invention comprises the following steps:

[0019] S1. For the phase change asphalt mixture large Marshall specimen, cut it radially to obtain a disc specimen with a thickness of 4 cm. Mark 8 points on the top surface of the specimen that are 4.5 cm away from the center of the top surface and are symmetrically distributed. Drill 8 through holes with a diameter of 2 cm along the thickness direction of the specimen with the 8 points as the center. Soak the specimen in water and put it in a constant temperature box at 20°C together with the test device for 6 hours;

[0020] S2. Screw 8 screws from bottom to top into the 8 circular holes on the bottom plate of the fan-shaped water tank, so that the top surface of the screws is flush with the bottom surface of the fan-shaped water tank and fits tightly. Adjust the angle and length of the 4 screw-type horizontal adjustment feet to keep the fan-shaped water tank level. Cut out 8 circular plastic films with a diameter of 1.5 cm, align the center of the film with the center of the top surface of the screw to fit the film to the top surface of the screw, and fix the part of the film that exceeds the edge of the screw on the fan-shaped water tank. Take out the test device and the disc sample from the constant temperature box, and inject the 20℃ water sample with an initial conductivity greater than 50μS / cm into the four leveled water tanks, so that the upper surface of the water film is flush with the upper edge of the water tank, forming water films with thicknesses of 1mm, 2mm, 3mm, and 4mm respectively. Align the 8 sample through holes with the 8 water tank through holes and place the disc sample on the water tank. Insert the pressure head unit into the sample through hole and make the incision depth of each pressure head consistent with the water film thickness below it. Rotate the pressure head so that the conductivity probe faces the center of the sample circle.

[0021] S3. Transfer the assembled sample and device to a -5℃ refrigerator and connect the conductivity meter. After 12 hours, draw the conductivity-time relationship curves of the four water film thicknesses respectively. The end time of the conductivity drop section is taken as the black ice condensation start time t 0i (i=1, 2, 3, 4) (min); put the device back into the constant temperature box at 20℃, and draw the relationship curves of water film conductivity and time in the four water tanks after 3h, and take the end time of the conductivity surge as the time when the black ice is completely melted t 1i (i=1, 2, 3, 4) (min); from (t 11 -t 01 )min、(t 12 -t 02 )min、(t 13 -t 03 )min、(t 14 -t 04 ) min, and the duration of black ice with thickness of 1 mm, 2 mm, 3 mm, and 4 mm on the phase change asphalt mixture was obtained respectively;

[0022] S4. Put the sample and the device back into the -5℃ refrigerator. For black ice with thickness of 1mm, 2mm, 3mm and 4mm, respectively, 01 +30)min、(t 02 +30)min、(t 03 +30)min、(t 04 +30)min, unscrew the screw in the through hole of each fan-shaped water tank by 1cm, and press the pressure head on it with a pressure gauge until the black ice breaks, and obtain the condensation strength S of the black ice 0i(i = 1, 2, 3, 4). After 12 hours, unscrew the screw in the other through hole of each fan-shaped water tank by 1 cm, and use a pressure gauge to measure the condensation strength S of the black ice of 4 thicknesses. 1i (i=1, 2, 3, 4).

[0023] Beneficial Effects of the Invention

[0024] (1) The present invention proposes a testing device for the duration and coagulation strength of black ice on a phase change asphalt pavement, which can accurately simulate water films of different thicknesses on the surface of the mixture.

[0025] (2) The present invention proposes a method for testing the duration and condensation strength of black ice on a phase-change asphalt pavement, which can accurately determine the moment when water freezes and ice melts.

[0026] (3) The present invention proposes a test method for the duration and coagulation strength of black ice on a phase change asphalt pavement, and proposes a new mechanical index to more effectively characterize the coagulation strength of black ice. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart of the test method.

[0028] Figure 2 It is a schematic diagram of the device of the present invention.

[0029] Figure 3 The conductivity change of 1mm water film at 0%, 1.0%, 1.5% and 2.0% phase change material dosage.

[0030] Figure 4 The condensation strength of 1mm black ice at 0%, 1.0%, 1.5% and 2.0% phase change material dosage. DETAILED DESCRIPTION

[0031] The specific implementation modes of the present invention are described to facilitate the understanding of the present invention by researchers in this technical field. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For ordinary researchers in this technical field, as long as various changes are within the scope of the spirit of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0032] Example

[0033] In this embodiment, the hollow round tube in the pressure head unit has a length of 6 cm, an outer diameter of 1.95 cm, a wall thickness of 5 mm, and is made of stainless steel. A through hole with a diameter of 5 mm is drilled on the side 1 cm from the top of the round tube using a high-precision drilling machine, and two symmetrical through holes with a diameter of 10 mm are drilled on the sides 2.5 cm and 4.5 cm from the top of the round tube, respectively. A straight groove tap is used to carve threads on the inner wall of the round tube within a range of 1 cm from the bottom.

[0034] In this embodiment, a round rod with a length of 10 mm and a cross-sectional diameter of 2 mm is used to cross a through-hole steel ball with a diameter of 6 mm and a through-hole diameter of 2 mm, and the two ends of the round rod with the steel ball are welded to the inner wall of a cylinder with a diameter of 10 mm and a height of 7 mm, and the sphere of the steel ball part exceeds the top surface of the cylinder. The two ends of a spring with a free length of 10 mm are respectively fixed on the bottom surfaces of the two cylinders, and the two round rods are parallel to each other after being fixed. The two connected cylinders are passed through the hollow tube through the symmetrical through holes on the hollow tube, and the two cylinders are both located in the two through holes, and the two round rods are parallel to the top surface of the hollow tube.

[0035] In this embodiment, the size of the small-diameter round tube in the concentric variable diameter special-shaped tube is 1 cm high, 1.9 cm outer diameter, and 5 mm wall thickness, the size of the large-diameter round tube is 2 cm high, 1.95 cm outer diameter, and 5 mm wall thickness, and the size of the disc is 1 cm thick and 1.9 cm in diameter, and the materials are all stainless steel. Use a cutting machine to open 8 incisions of equal depth on the side of the large-diameter round tube along the height direction. Use a thread cutter to carve threads on the outer side of the small-diameter round tube, and use a straight groove tap to carve threads on the inner wall of the large-diameter round tube within 1 cm from the upper edge of the incision and on the side of the disc. After using a laser engraving machine and a punching machine to carve a "cross"-shaped groove with a length of 3 mm, a width of 3 mm, and a depth of 1 mm on the bottom of the disc and drill a through hole with a diameter of 4 mm, use a cross screwdriver to screw the disc into the large-diameter round tube, and after tightening, the bottom of the disc is flush with the upper edge of the incision.

[0036] In this embodiment, the conductivity meter used is a DDS-307 conductivity tester, whose test range is 0.0μS / cm-299.9μS / cm, applicable temperature range is -10℃~60℃, and the number of channels is 8. The conductivity probe is inserted into the pressure head from the circular hole 1cm away from the top of the hollow circular tube on the side of the circular tube. After ensuring that the bottom end of the probe is flush with the lower edge of the large-diameter circular tube cutout, the probe is fixed to the inner wall of the hollow circular tube and the concentric variable-diameter special-shaped tube from top to bottom with glue.

[0037] In this embodiment, a laser engraving machine is used to engrave the top surface of a stainless steel cylinder with a diameter of 15 cm and a height of 6 cm, forming four 90° sector-shaped water tanks with a radius of 7.2 cm in the water tank unit, a "cross" frame with a length of 14.6 cm, a width of 14.6 cm, and a thickness of 2 mm between the water tanks, and a circular frame with a thickness of 2 mm on the outside of the water tank. The depths of the four water tanks are 1 mm, 2 mm, 3 mm, and 4 mm, respectively. A cutting machine is used to cut off four sector-shaped columns in the middle of the cylinder, and the top surfaces are sectors 2 cm away from the bottom surfaces of the four water tanks, and the bottom surfaces are sectors 1 cm away from the bottom surfaces of the cylinders, finally forming the water tank bottom plate at the top, the "cross" frame in the middle, and the cylindrical bottom plate at the bottom.

[0038] In this embodiment, two points are marked on the surface of each sector-shaped water tank, with a distance of 4.36 cm from the sector vertex and a vertical distance of 1.67 cm from the nearest sector radius. Two through holes with a diameter of 2 cm and the two points as the center are punched out with a puncher, and each through hole is equipped with a screw with a screw length of 2 cm. On each sector of the cylindrical bottom plate surface, a point located on the sector angle bisector and 5 cm away from the sector vertex is marked, and a through hole with a diameter of 1 cm and the point as the center is punched out with a puncher, and each through hole is equipped with a screw-type horizontal adjustment foot.

[0039] In this embodiment, glass wool with a thickness of 2 cm is glued to the side of the fan-shaped water tank top plate.

[0040] In this embodiment, a pair of mutually perpendicular horizontal rulers are installed on two adjacent sector-shaped surfaces of the cylindrical bottom plate.

[0041] In this embodiment, the phase change material used is tetradecane and the wall material is silicon dioxide (SiO 2 ), the prepared composite phase change material tetradecane / SiO 2 , its properties are shown in Table 1, where T start 、T end , ΔH m represent the starting temperature, ending temperature and enthalpy of phase transition during the cooling process. 2 The content of phase change asphalt mixture is 0%, 1%, 1.5%, 2%, the mixture type is SMA-13, and the design gradation is shown in Table 2. The specimen is cut along the radial direction by a cutting machine, and a 4cm high disc specimen is cut from the middle of the specimen. The specimen is punched with a drilling machine, with a total of 8 holes with a hole diameter of 2cm. The distance between the center of the 8 holes and the center of the cross section of the specimen is 4.5cm, and they are symmetrically distributed. The specimen is soaked in local tap water in Nanjing for 6h.

[0042] Table 1 Composite phase change materials tetradecane / SiO 2 Technical nature

[0043]

[0044] Table 2 SMA-13 ​​design gradation

[0045]

[0046] In this embodiment, an Allen wrench is used to screw 8 screws into the 8 round holes of the fan-shaped water tank from bottom to top, so that the top surface of the screws is flush with the bottom surface of the water tank, and the 4 screw-type leveling feet are adjusted to ensure that the fan-shaped water tank remains level; the plastic wrap is cut into 8 circular plastic films with a diameter of 2.5 cm, and the film is attached to the top surface of the screw by aligning the center of the film with the center of the top surface of the screw, and then 502 glue is used to stick the part of the film that exceeds the edge of the screw to the bottom surface of the water tank.

[0047] In this example, the initial conductivity of local tap water in Nanjing is 120±10μS / cm, and the curing box and refrigerator used are YH-40B curing box and BD-100DTEC refrigerator respectively. 2 The conductivity changes of water films of different thickness on the surface of phase change asphalt mixture with contents of 0, 1%, 1.5% and 2% in a -5℃ environment. Figure 3 The conductivity curve of the 1mm thick water film on the surface of the phase change asphalt mixture sample under different phase change material dosages is shown in the figure. As shown in the figure, the end time of the sudden drop and sudden rise of the surface water film conductivity of the phase change asphalt mixture samples with 0%, 1%, 1.5%, and 2% is 60min, 95min, 125min, 145min and 805min, 790min, 765min, 745min, respectively, which shows that the specimens added with phase change materials at -5℃ can effectively delay the freezing time of the surface water film, accelerate the melting of black ice, and greatly reduce the duration of black ice.

[0048] In this embodiment, the pressure gauge used is a NK-200 pressure gauge with a range of 2.5MPa and an accuracy of 0.02MPa. Phase change asphalt mixtures with a phase change material content of 0%, 1%, 1.5%, and 2% were tested respectively. The condensation strength of the 1mm thick water film on the surface of the sample after 30 minutes of freezing and 12 hours of freezing. Among them, it can be seen from the above that the time of 30 minutes after the water film of the four mixtures is frozen is 90min, 125min, 155min, and 175min respectively. Figure 4 The condensation strength of 1mm thick black ice on the surface of asphalt mixture at two time points under four dosages of phase change material. As shown in the figure, the longer the freezing time, the greater the condensation strength of black ice. Phase change material can effectively reduce the condensation strength of black ice, and the higher the dosage of phase change material in asphalt mixture, the lower the condensation strength of black ice on the surface of the mixture.

Claims

1. Test device for the duration and condensation strength of black ice on phase change asphalt pavement, including: Pressure head unit, water tank unit and collection unit. The pressure head unit is a hollow round tube with a length of 6 cm and an outer diameter of 1.95 cm at the top, with a through hole of 5 mm in diameter on the side 1 cm away from the top, and a thread is provided on the inner wall of the round tube within 1 cm from the bottom; the lower part of the pressure head is a concentric variable diameter special-shaped tube, with a thread provided on the outer side of the small-diameter round tube, which extends into the inside of the hollow round tube and is screwed with the thread on the inner wall of the hollow round tube, the outer diameter of the large-diameter round tube is the same as that of the hollow round tube, and 8 incisions of equal depth are provided on the side along the height direction, and the inner wall of the large-diameter round tube is provided with a thread within 1 cm from the upper edge of the incision, and is equipped with a disc that can be screwed therewith, and the side and bottom of the disc are respectively engraved with external threads and "cross"-shaped grooves, and after tightening, the bottom surface of the disc is flush with the upper edge of the incision; the inside of the pressure head is equipped with a conductivity probe, and the probe enters the pressure head from the through hole on the hollow round tube 1 cm away from the top, and the bottom of the probe is flush with the lower edge of the incision. The water tank unit is composed of 4 open fan-shaped water tanks with equal horizontal areas. The depths of the fan-shaped water tanks are 1mm, 2mm, 3mm, and 4mm respectively. The bottom plate thickness of each fan-shaped water tank is 2cm, and there are two through holes on the bottom plate with a hole diameter of 2cm. The inner wall of the hole is threaded, and each hole is equipped with a screw that can be screwed thereto. After tightening, the top surface of the screw is flush with the bottom surface of the water tank. The water tank is made of stainless steel, and glass wool with low thermal conductivity is pasted on the outer side.

2. The testing device for the duration and condensation strength of black ice on a phase change asphalt pavement according to claim 1 is characterized in that: The pressure head unit consists of 4 groups, each group has 2 pressure heads, and the depths of the side cuts of the large-diameter circular tubes in each group of pressure heads are 1mm, 2mm, 3mm, and 4mm respectively.

3. The testing device for the duration and condensation strength of black ice on a phase change asphalt pavement according to claim 1 is characterized in that: The distances between the centers of the two through holes on the bottom plate of the fan-shaped water tank and the vertex of the fan are both 4.36 cm, and the vertical distances to the nearest fan radius are both 1.67 cm.

4. The test method for the duration and condensation strength of black ice on a phase change asphalt pavement comprises the following steps: S1. For the phase change asphalt mixture large Marshall specimen, cut it radially to obtain a disc specimen with a thickness of 4 cm. Mark 8 points on the top surface of the specimen that are 4.5 cm away from the center of the top surface and are symmetrically distributed. Drill 8 through holes with a diameter of 2 cm along the thickness direction of the specimen with the 8 points as the center. Soak the specimen in water and put it in a constant temperature box at 20°C together with the test device for 6 hours; S2. Take out the test device and disc sample from the thermostat, and inject the 20℃ water sample with an initial conductivity greater than 50μS / cm into the four leveled water tanks, so that the upper surface of the water film is flush with the upper edge of the water tank, and form water films with thicknesses of 1mm, 2mm, 3mm, and 4mm in the four water tanks, respectively. Place the phase change asphalt mixture disc sample on the water tank, and align the 8 sample through holes with the 8 water tank through holes. Insert the pressure head unit into the sample through hole, and make the cut depth of each pressure head consistent with the thickness of the water film below it, and rotate the pressure head so that the conductivity probe faces the center of the sample circle; S3. Transfer the assembled sample and device to a -5℃ refrigerator and connect the conductivity meter. After 12 hours, draw the conductivity-time relationship curves of the four water film thicknesses respectively. The end time of the conductivity drop section is taken as the black ice condensation start time t 0i (i=1, 2, 3, 4) (min); put the device back into the constant temperature box at 20℃, and draw the relationship curves of water film conductivity and time in the four water tanks after 3h, and take the end time of the conductivity surge as the time when the black ice is completely melted t 1i (i=1, 2, 3, 4) (min); from (t 11 -t 01 )min、(t 12 -t 02 )min、(t 13 -t 03 )min、(t 14 -t 04 ) min, and the duration of black ice with thickness of 1 mm, 2 mm, 3 mm, and 4 mm on the phase change asphalt mixture was obtained respectively; S4. Put the sample and the device back into the -5℃ refrigerator. For black ice with thickness of 1mm, 2mm, 3mm and 4mm, respectively, 01 +30)min、(t 02 +30)min、(t 03 +30)min、(t 04 +30)min, unscrew the screw in a through hole of each fan-shaped water tank by 0.5cm~1cm, and press the pressure head on it with a pressure gauge until the black ice breaks, and obtain the condensation strength S of the black ice. 0i (i=1, 2, 3, 4). After 12 hours, unscrew the screw in the other through hole of each fan-shaped water tank, and use a pressure gauge to measure the condensation strength S of the black ice of four thicknesses. 1i (i=1, 2, 3, 4).

Citation Information

Patent Citations

  • Rut testing device for asphalt mixture of mountain roads and method thereof

    CN102445397A

  • Snowmelt long-term efficacy testing method of snowmelt asphalt mixture

    CN104237323A

  • Ice core conductivity measurement workbench

    CN107064640A

  • Road surface condition detection device and method

    CN109764913A

  • Roadway freezing point monitoring system and method

    CN1615432A